In vivo studies of substances used in the cosmetic industry - Igielska-Kalwat, Joanna; Gościańska, Joanna; Witkowska, Beata; Nowak, Izabela (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Cosmetic producers are obliged to guarantee the safety and stability of their products. The current legal regulations are based on the European Union Directive (1223/2009) of 30 November 2009. The main aim of the directive is to formulate criteria of safety of a cosmetic product and requirements that it must meet to be placed on the market. A new cosmetic product is subjected to thorough investigation prior to its introduction on the market. It should be studied not only with respect to its safety, but also with respect to its effectiveness declared by the producer. The studies are performed in vivo , by the contact or epidermal patch tests on the human skin.